Amorphous Nickel‐Cobalt‐Borate Nanosheet Arrays for Efficient and Durable Water Oxidation Electrocatalysis under Near‐Neutral Conditions. Issue 41 (3rd July 2017) - Chen, Lanlan; Ren, Xiang; Teng, Wanqing; Shi, Pengfei
Abstract: Electrolytic hydrogen generation needs earth‐abundant oxygen evolution reaction electrocatalysts that perform efficiently at mild pH. Here, the development of amorphous nickel‐cobalt‐borate nanosheet arrays on macroporous nickel foam (NiCo‐Bi/NF) as a 3D catalyst electrode for high‐performance water oxidation in near‐neutral media is reported. To drive a current density of 10 mA cm −2, the resulting NiCo‐Bi/NF demands an overpotential of only 430 mV in 0.1 m potassium borate (K‐Bi, pH 9.2). Moreover, it also shows long‐term electrochemical durability with maintenance of catalytic activity for 20 h, achieving a high turnover frequency of 0.21 s −1 at an overpotential of 550 mV. Abstract : NiCo‐Bi nanosheet arrays on nickel foam support behaves as 3D catalyst electrode for water oxidation at near‐neutral pH. This electrode achieves a catalytic current density of 10 mA cm −2 at an overpotential of 430 mV with strong electrochemical stability in 0.1 m K‐Bi.